BENTUK DAN FUNGSI TINDAK TUTUR ILOKUSI DALAM TEKS MAKKOBAR - ilham sahdi lubis (Institut Pendidikan Tapanuli Selatan, 2018)
This study aims to analyze the form and function of illocution speech acts used in ‘Teks Makkobar’. This study uses descriptive qualitative research. Sources of data in this study are ‘Teks Makkobar’. Data collection used in this study is referring method. Referring method has basic techniques such as tapping techniques. Furthermore, this tapping technique is followed by advanced techniques in the form of a technique called by ‘libat cakap’ and record techniques. To obtain the validity of data in the research required inspection techniques. The results of this study indicate that there are three forms of illocution speech acts contained in the ‘Teks Makkobar’, the form of speech acts include, the form of assertive, directive and expressive speech acts. There are three functions of illocution speech acts is requesting, pardoning and stating.